Analysis Of Internal Transformation Implementation at The Planning and Budgeting Bureau Of The Ministry Of Health (Case Study 2022-2023) - Razali, Roni; Siswoyo, Mardi (LPPM Universitas PGRI Sumatera Barat, 2023)
Undang-Undang Dasar 1945 pasal 28 H and Undang-Undang Nomor 17 Tahun 2023 on Health stipulate that everyone has the right to health services. Therefore, every individual, family, and community has the right to protection for their health, and the state is responsible for ensuring that the right to a healthy life is fulfilled for its population, including for the poor and underprivileged. Organizationally, like most bureaucratic institutions, the challenge of improving professionalism is an inevitability in responding to health development challenges. This study aims to analyze the extent of internal transformation implementation at the Planning and Budgeting Bureau of the Ministry of Health, using a systems approach. The input variables consist of human resources, financing, regulations, and guidance. The process variables include planning, talent management, capacity building, and the implementation of a corporate university. The output variable is the realization of internal transformation at the Ministry of Health. This research was conducted at the Planning and Budgeting Bureau using a qualitative approach, with primary data collected through in-depth interviews with several informants and a review of relevant supporting documents. The results of the study indicate that transformation cannot effectively proceed without the role of all employees, thus the main actors in internal transformation are all employees. Internal transformation encourages the enhancement of collaboration and teamwork abilities, with adaptability and resilience serving as strong foundations in facing changes and challenges. Internal transformation positively impacts individual growth and development within the organization. One key to talent development is improving communication competencies. Based on these findings, it is recommended that for the implementation of internal transformation to proceed effectively, the involvement of all human resources in the organization must be sufficient and competent. Additionally, to enhance cultural change, recognition and rewards should be given to individuals and teams who positively contribute to the transformation process.